Concerning Foreign Migrants’ Integration in Russian Empire - Т. A. Bazhan (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article deals with the possibility to use historical experience of pre-revolutionary Russia to develop state policy in the migration sphere. During centuries of multinational and multicultural society formation a vast and unique integration experience was acquired. It promoted unity and integrity of the country, its development and geo-political interests. In general policy of Russian empire demonstrated consistency in resolving problems of home and foreign migration, clear understanding of goals aimed at ensuring country’s interests. The effective state system gave an opportunity to help migrants, to control their stay, to regulate migration flows, to provide differentiated approach to various categories of foreigners and internally displaced persons. Today’s migration policy in Russia is more complicated as we have an ineffective system of social and cultural adaptation and integration of foreign migrants, which requires serious optimization and building the centralized infrastructure. The objective and critical interpretation of home experience of the past carried out by the author could enrich academic support of migration policy at the current stage and create the efficient system of migrants’ inclusion in the host society.